2018
DOI: 10.12944/cwe.13.1.03
|View full text |Cite
|
Sign up to set email alerts
|

Human Health Risk Assessment of Heavy Metals in the Black Sea: Evaluating Mussels

Abstract: The levels of Fe, Zn, Mn, Cu, Pb, Cd and Hg in the edible tissues of Mytilus galloprovincialis Lamarck, 1819 (Mediterranean mussel) picked up from the Black Sea coasts of Turkey have been determined by Inductively Coupled Plasma -Mass Spectrometer (ICP/MS) with a view to biomonitoring metal contamination in 2015. In this work, a statistically significant difference in the amounts of all studied heavy metals analyzed was noticed amidst sampling areas namely Igneada, Sinop, Samsun and Trabzon so that appraise we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 28 publications
0
6
2
Order By: Relevance
“…This result is in agreement with that of Olmedo et al's [46] study which found 3.25 mg/60 kg person/week (0.464 × 7) of Zn intake through fish and shellfish consumption in Andalusia (Southern Spain). The current result is lower than that in [47] which reported that the EWI of the Pb in M. galloprovincialis ranged from 3.92 to 13.23 mg/70 kg person/week (0.056 × 70 to 0.189 × 70) with the EWI : PTWI ratio of 0.86 to 2.70%.…”
Section: Resultscontrasting
confidence: 92%
See 3 more Smart Citations
“…This result is in agreement with that of Olmedo et al's [46] study which found 3.25 mg/60 kg person/week (0.464 × 7) of Zn intake through fish and shellfish consumption in Andalusia (Southern Spain). The current result is lower than that in [47] which reported that the EWI of the Pb in M. galloprovincialis ranged from 3.92 to 13.23 mg/70 kg person/week (0.056 × 70 to 0.189 × 70) with the EWI : PTWI ratio of 0.86 to 2.70%.…”
Section: Resultscontrasting
confidence: 92%
“…The current result is found to be higher than that of the study by Olmedo et al [46], who reported 0.35 mg/60 kg person/week (0.05 × 7) of Mn intake through fish and shellfish consumption in Andalusia. The current result is also found to be slightly higher than that of the study by Bat et al [47] who reported that EWI of the Mn in M. galloprovincialis was in the range of 1.37 to 2.21 mg/70 kg person/week (0.0196 × 70 to 0.0315 × 70).…”
Section: Resultscontrasting
confidence: 88%
See 2 more Smart Citations
“…Numerous studies on the concentration of trace elements in mussels assessed risks associated with their consumption collected in the world regions of modern large-scale producers of cultivated molluscs (for example, Montenegro, Turkey, China, USA, Italy, New Zeland, Malaysia: Stankovic et al, 2012;Bat et al, 2018;Fung et al, 2004;Ho and Leung, 2014;Goldhaber, 2003;Spada et al, 2013;Whyte et al, 2009;Yap et al, 2016). Usually, they focused on key pollutants, namely, on four trace elements (Cd, Pb, Hg, and As) and discussed their concentrations in mussels in comparison with guideline limits.…”
Section: Application Of Mussels In Risk Assessmentmentioning
confidence: 99%